Estimation of Water Stress in Guinea and Sudano-Sahelian Ecological Zones of Nigeria Under Climate Change and Population Growth - A. C, Salihu; A, Abdulkadir; G. N, Nsofor; M. Y, Otache (International Journal of Hydrology Research, 2020)
Climate change and population growth are seen to be the major factors that will shape the pattern of per capita water up to the end of 21st century. The study aimed to project water stress condition in Guinea and Sudano-Sahelian ecological zones of Nigeria under the impacts of climate change and population growth. Firstly, annual water yield was generated using KNMI climate explorer for (2019-2048), (2049-2078) and (2079-2100) under three CO2 emission trajectories. Secondly, population was projected using the Nigeria’s average growth rate of 2.6%. Thirdly, the per capita water was analysed based on water stress index. Mann-Kendal statistical test was used to analyses trends in water stress at 0.05 significant levels. Result demonstrated that the Guinea and Sudano-Sahelian ecological zones of Nigeria will experience significant positive trend in water stress with respect to climate change impact for mid and long-term periods whereas no significant trend under the short-term projection. However, regional trend analysis under the influence of population growth at constant climate observed that there were significant positive trends in water stress for the three projected periods. More so, the same positive trends were obtained under the combined impacts of climate change and population growth in Guinea and Sudano-Sahelian ecological zones of Nigeria. This implies that future water scarcity is imminent and will primarily cause by population growth and secondarily by climate change in the area. The results can act as guidelines for strategic planning for adaptive and mitigation measures to water stress as envisaged by the projection.